Pathogenicity and autodissemination of promising entomopathogenic fungi strains on Rhynchophorus palmarum L. (Coleoptera: Dryophthoridae) - León-Martínez, Guillermo Adolfo; Campos-Pinzón, Juan Carlos; Arguelles-Cárdenas, Jorge Humberto (Agronomía Mesoamericana, 2019)
Introduction. In Latin America, the weevil (Rhynchophorus palmarum L.) is an important pest of oil palm and coconut palm because it is associated with the transmission of red ring (RRD) and bud rot (BR); diseases that cause high management costs and mortality of plantations; the entomopathogens Metarhizium anisopliae and Beauveria bassiana (Hypocreales: Clavicipitaceae) represent an microbiological control alternative. Objective. The objective of this work was to determine the pathogenicity of promising strains of M. anisopliae and B. bassiana on adults of R. palmarum and to evaluate the spread of the best strains, from inoculated weevil male adults to not-inoculated females. Materials and methods. The study was carried out in two phases in the La Libertad Research Center of the Corporación Colombiana de Investigación Agropecuaria (AGROSAVIA), Department of Meta, Colombia through factorial arrangements in completely random designs; in the first one, four strains of M. anisopliae, one of B. bassiana, and one commercial product based on M. anisopliae were evaluated; in the second one, to determine the self-dissemination of the entomopathogen, the two highest effectiveness strains from the first experiment (CPMa1104 and Mt008) were evaluated by two methods of application to males (immersion and powder). Results. The CPMa1104 strain showed the highest efficacy (1x104 and 1x108 conidia ml-1), followed by Mt008 (1x108 conidia ml-1) with mortalities of 78.6 % and 67.9 %, respectively. Contact dissemination capacity of M. anisopliae strains CPMa1104 and Mt008 was observed from inoculated male adults to non-inoculate females. Female mortality reached 100 % when the males were inoculated with powdered CPMa1104. Conclusion. The dissemination of CPMa1104 and Mt008 strains of M. anisopliae by inoculated males to non-inoculated females was tested, which makes the use of this entomopathogen a promising control alternative.